Chamaejasmenin B, an Inhibitor for Metastatic Outgrowth, Reversed M2-Dominant Macrophage Polarization in Breast Tumor Microenvironment - Li, Qi; Sun, Lidong; Liu, Li; Ran, Qingsen; Du, Xinke; Yang, Qing; Wang, Yajie; Li, Yujie; Chen, Ying; Weng, Xiaogang; Cai, Weiyan; Zhu, Xiaoxin (Frontiers in Immunology, 2021)
Metastasis is a multi-step process that depends on the interactions between tumor cells and their microenvironment. Macrophages in the tumor microenvironment show high polarization plasticity and have a paradoxical role in cancer progression. Hijacked by tumor-promoting signals, the polarization status of macrophages was pathologically disturbed and believed to be the decisive mechanism forcing the progression of metastasis. In this study, we explored the immunological activity of Chamaejasmin B (ICJ), a previously-proved inhibitor for metastasis, in macrophages from metastatic microenvironment. When intravenously injected of 4T1 cells in mice, ICJ significantly inhibited its metastatic outgrowth. Taking tumor cell and macrophage as a functional integrity, an adoptive transfer model was established in vitro to exclude the direct effect of ICJ on tumor. The findings suggest a dual influence of ICJ on both tumors and macrophages, as indicated by the rebalance of macrophage polarization and suppression of clonogenic potential in tumor cells. Mechanistically, ICJ redirected M2-dominant polarization of tumor associated macrophage in an IL4-mTOR-dependent manner. Collectively, our study revealed that ICJ rebalanced macrophage polarization in malignant microenvironment and showed promising effect in suppressing metastatic outgrowth in breast cancer model.